Modern Teaching Versus Traditional Teaching- Albanian Teachers Between Challenges and Choices - Balliu, Valbona (European Journal of Multidisciplinary Studies, 2017)
Education lies in the foundations of the nation. Providing knowledge to generations, consolidating their future, inspiring them to incarnate benevolence and esteem splendor, valor and good principles has been one of the oldest professions of mankind, the noblest and the most difficult tasks. It is very significant that Albania and its schools have been subject of this paper. The 25-year period of the country’s transition and the opening of the Albanian society to the Western World Modernization brought profound changes to the Albanian education institutions, in terms of the curricula, management and the teaching processes. The greatest part of teachers in Albania was educated during the communist period, where pedant and traditional teaching prevailed, mainly deriving from the Russian Academics. Traditional methods consider teachers as the center of the teaching process; as well as managers and the main and referential source of the scientific information. Novelties in the teaching-learning methods applied by Western Schools focus on student centered teaching; they create a variety of situations in which students evolve critical thinking. These methods have been acquired by teachers but, in the conclusions of our paper we noticed that, occasionally, they applied traditional teaching methods (especially in the scientific subjects). There is still space and worth for discussion regarding traditional teaching methods versus the modern ones. Various scholars have considered traditional teaching as the method developing theoretical thinking, whereas modern teaching develops practical skills, pragmatist and able to be oriented to the frenetic development of the world. Teachers, especially those teaching subjects like mathematics, physics and chemistry, consider traditional teaching to be more serious since students achieve better results in these subjects when outdated teaching methods have been applied. This paper and its conclusions can be considered interesting since confrontation of ideas regarding teaching methods remains a challenge for all teachers.